Development of Oleogel-Based Fat Replacer and Its Application in Pan Bread Making - Sung-Huo Kim; Yeon-Ji Jo; Sung Ho Lee; Sung-Hoon Park (Foods, 2024)
In recent years, the bakery industry has been exploring alternative fats to replace traditional solid fats. Shortening, a common baking ingredient, is produced through the hydrogenation of vegetable oils, resulting in high levels of saturated and trans fatty acids, despite its vegetable oil origin. The excessive consumption of these fats has been associated with negative health effects, including dyslipidemia and cardiovascular issues. Oleogels, incorporating hydroxypropyl methylcellulose (HPMC), xanthan gum (XG), and olive oil, were utilized to replace shortening in the production of white pan bread. The substitution of shortening with oleogel in the white pan bread preparation demonstrated potential reductions in saturated fat, trans fat, and the ratio of saturated fat to unsaturated fatty acids. Specifically, with the complete substitution of shortening with oleogel, saturated fatty acids decreased by 52.46% and trans fatty acids by 75.72%, with unsaturated fatty acids increasing by 57.18%. Our findings revealed no significant difference in volume between bread made with shortening and bread with up to 50% shortening substitution. Moreover, when compared to bread made with shortening and 50% oleogel substitution, no adverse effects on the quality characteristics of volume and expansion properties were observed, and the retrogradation rate was delayed. This study suggests that incorporating oleogels, formed with hydrocolloids such as HPMC and XG, to replace shortening in bread, in conjunction with traditional solid fats, provides positive effects on the quality and nutritional aspects of the bread compared to using oleogel alone. Through this study, we demonstrate the use of oleogels as a healthier alternative to shortening, without reducing the bread’s quality, thus offering a practical solution to reduce unhealthy fats in bakery products.